Clinical Features of Cluster Headache: An Outpatient Clinic Study from China. Issue 6 (30th April 2013) - Xie, Qianyun; Huang, Qingqing; Wang, Jing; Li, Nan; Tan, Ge; Zhou, Jiying
Abstract Objective. The aim of this study was to investigate the clinical characteristics of cluster headache (CH) in a neurology outpatient population in China. Methods. A cross‐sectional survey was conducted from June to December 2011 in a tertiary care, university‐affiliated hospital. All consecutive patients citing headache as their chief complaint were asked to participate in a face‐to‐face interview with a qualified headache specialist and to complete a detailed self‐administered questionnaire. The diagnosis of CH was made according to the International Classification of Headache Disorders, Second Edition (ICHD‐II). Results. Of the 1, 526 headache patients screened, 26 were diagnosed with CH (6 women, 20 men). Mean age at onset was 27 ± 8 years (range, 17–47), and 50% of patients were 20–30 years of age. Of the 26 CH patients, 61.5% reported that pain was usually centered at the right temporal region, and 69.2% characterized the pain as swelling. Attacks lasted 87 minutes on average and were associated with cranial autonomic symptoms (100%). A seasonal predilection was reported by 69.2% of CH patients. No patient reported significant changes in pain severity after physical activity. Tobacco use was common (14/26 patients), and alcohol was the most frequently cited trigger. Conclusions. This study details the clinical features of CH in a neurology outpatient population in China. Compared with Western studies, our patients were different in several aspects including the absence of chronic CH.